Low-warpage multilayer ceramic substrate and preparation method thereof
By leveraging the synergistic effect of modified SiC particles and zirconia whiskers, the problem of insufficient mechanical properties in low-warpage ceramic substrates was solved, improving fracture toughness and bending strength while reducing warpage, thus achieving high-strength and high-toughness multilayer ceramic substrates.
Patent Information
- Application Number
- CN202511438400.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-10-10
AI Technical Summary
The existing low-warpage ceramic substrates have insufficient mechanical properties, especially poor bending strength and fracture toughness, mainly due to stress concentration problems caused by increased porosity and uneven grain growth.
Modified SiC particles and zirconia whiskers are used in combination. The SiC particles are coated with silica and alumina to enhance their dispersibility in the slurry and their compatibility with the matrix material. In addition, additives such as hexadecyltrimethylammonium bromide, polyethylene glycol, and polyvinyl butyral are combined to improve the bonding and dispersion between particles.
The mechanical properties of multilayer ceramic substrates, including fracture toughness and flexural strength, are significantly improved, while warpage is reduced, resulting in high-strength and high-toughness multilayer ceramic substrates.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of ceramic substrate, in particular, relates to a low warpage multilayer ceramic substrate and a preparation method thereof. BACKGROUND
[0002] Ceramic materials are widely used in high-end fields such as machinery, chemistry, energy, aerospace, biomedicine due to their excellent physical and chemical properties. In the packaging of power devices, ceramic substrate is a commonly used material, among which, using alumina ceramic substrate as packaging material can provide a series of excellent performances such as good bottom support, high insulation performance, low dielectric loss and dielectric constant, and high thermal conductivity. However, the current low warpage ceramic substrate has the problem of poor mechanical properties, because in order to realize low warpage, the existing process usually adjusts the ceramic composition or microstructure to reduce the thermal expansion coefficient of the substrate, but these adjustments often lead to a decrease in the density of the ceramic, resulting in problems such as increased porosity and uneven grain growth during sintering. As stress concentration points, pores can significantly reduce the bending strength and fracture toughness of the substrate. Therefore, there is an urgent need for a low warpage multilayer ceramic substrate with high toughness and high strength. SUMMARY
[0003] The present application provides a low warpage multilayer ceramic substrate and a preparation method thereof, which solves the problem of insufficient mechanical properties of the low warpage multilayer ceramic substrate in the related art.
[0004] The technical scheme of the present application is as follows: The present application provides a low warpage multilayer ceramic substrate, which comprises the following raw materials by weight: 90-110 parts of alumina, 3-4 parts of dispersant, 4-6 parts of plasticizer, 10-12 parts of binder, 3-4 parts of sintering aid, 70-80 parts of solvent, and 6-9 parts of functional aid. The functional aid comprises modified SiC particles. The modified SiC particles are obtained by successively coating SiC particles with SiO2 and Al2O3.
[0005] As a further technical scheme, the preparation method of the modified SiC particles comprises the following steps: A1, dispersing SiC powder in ethanol, adding ammonia water to adjust the pH to 7.5-9.5, adding tetraethyl orthosilicate dropwise, stirring, centrifuging, alcohol washing, and drying to obtain SiO2-coated SiC particles; A2, dispersing the SiO2-coated SiC particles in water, adding a buffer solution, then adding Al(NO3)3 solution dropwise, ultrasonicating, stirring, adding ammonia water to adjust the pH to 6.5-7.5, and then heating, alcohol washing, and drying to obtain modified SiC particles.
[0006] As a further technical solution, the buffer solution comprises an acetic acid-sodium acetate solution.
[0007] As a further technical solution, in step A1, the stirring temperature is 40-50℃, and the stirring time is 4-4.5h. In step A2, the temperature of the heat preservation is 70-80℃, and the heat preservation time is 30-40min.
[0008] As a further technical solution, the mass-volume ratio of the SiC powder and ethanol is 1g:300mL.
[0009] As a further technical solution, the mass-volume ratio of the SiC powder and tetraethyl orthosilicate is 1g:3-5mL. The concentration of the Al(NO3)3 solution is 0.1-0.2mol / L.
[0010] As a further technical solution, the mass-volume ratio of the SiO2-coated SiC particles and the Al(NO3)3 solution is 1g:100-110mL. Preferably, the mass-volume ratio of the SiO2-coated SiC particles and water is 1g:100mL.
[0011] As a further technical solution, the mass-volume ratio of the SiO2-coated SiC particles and the buffer solution is 1g:8-10mL. Preferably, the mass-volume ratio of the SiO2-coated SiC particles and the buffer solution is 1g:10mL.
[0012] As a further technical solution, in steps A1 and A2, the mass fraction of the ammonia water is independently 25wt%-28wt%. Preferably, in steps A1 and A2, the mass fraction of the ammonia water is independently 26wt%.
[0013] As a further technical solution, the dropping speed of the tetraethyl orthosilicate is 0.15-0.2mL / min. In step A2, the dropping speed of the Al(NO3)3 solution is 3-3.5mL / min.
[0014] As a further technical solution, the concentration of the Al(NO3)3 solution is 0.1-0.2mol / L. Preferably, the concentration of the Al(NO3)3 solution is 0.15mol / L.
[0015] As a further technical solution, the functional additive further comprises zirconia whiskers.
[0016] The modified SiC particles and the zirconia whiskers are used in combination in the low-warp multilayer ceramic substrate, and the mechanical properties of the ceramic substrate are further improved through the synergistic effect of the particles and the whiskers.
[0017] As a further technical solution, the mass ratio of the modified SiC particles and the zirconia whiskers is 1:1 to 2.
[0018] In the application, the mechanical properties of the ceramic substrate are further improved by adjusting the mass ratio of the modified SiC particles and the zirconia whiskers, and the mass ratio of the modified SiC particles and the zirconia whiskers is 1:1 to 2.
[0019] As a further technical solution, the sintering aid includes one or both of magnesium oxide and calcium oxide. The solvent includes one or both of ethanol and isopropyl alcohol.
[0020] As a further technical solution, the dispersant includes cetyltrimethylammonium bromide.
[0021] In the low-warp multilayer ceramic substrate, cetyltrimethylammonium bromide is added as a dispersant, cetyltrimethylammonium bromide is a cationic surfactant, can adsorb particles in the slurry, make them positively charged, the positive charge can generate electrostatic repulsion, thereby preventing particle agglomeration, making the particles more uniformly dispersed, and thereby improving the mechanical properties of the ceramic substrate.
[0022] The plasticizer includes one or both of polyethylene glycol and glycerol.
[0023] In the low-warp multilayer ceramic substrate, polyethylene glycol and glycerol are added as plasticizers, the polyethylene glycol molecular chain contains a large number of ether bonds, such groups can form hydrogen bonds with active groups such as hydroxyl groups on the surface of ceramic particles, and at the same time, the linear long-chain structure can fill the gaps between ceramic particles, weaken the interaction force between particles, and ultimately improve the plasticity of the ceramic body; the glycerol molecule contains three hydroxyl groups, can form a hydration film on the surface of ceramic particles, can significantly reduce the frictional resistance between particles, reduce the resistance to relative movement of particles, and can enhance the bonding strength between particles, to ensure that the ceramic substrate has good mechanical properties.
[0024] As a further technical solution, the binder includes polyvinyl butyral.
[0025] In the low-warp multilayer ceramic substrate, polyvinyl butyral is added as a binder, the polyvinyl butyral molecular chain contains a variety of functional groups such as hydroxyl groups and acetal groups, these functional groups can be tightly combined with atoms or groups on the surface of particles in the slurry through hydrogen bonds and van der Waals forces, thereby bonding the particles in the slurry together, and making the ceramic substrate have good mechanical properties.
[0026] The application further provides a preparation method of the low-warp multilayer ceramic substrate. S1, mixing raw materials, casting, drying, and obtaining green ceramic sheets; S2, punching and filling holes of the green ceramic sheets, performing surface printing, laminating and pressing, up-down conduction, cutting, sintering, and cooling, and obtaining the low-warp multilayer ceramic substrate.
[0027] The working principle and advantages of the application are as follows: In the application, the mechanical properties of the prepared multilayer ceramic substrate are enhanced by using SiC particles coated with silicon dioxide and aluminum oxide in sequence. On the one hand, the dispersibility of the SiC particles in the slurry is improved by coating the SiC particles with silicon dioxide, thereby improving the mechanical properties of the prepared ceramic substrate. On the other hand, the SiC particles are further coated with aluminum oxide, and since the matrix material of the ceramic substrate is aluminum oxide, the compatibility with the matrix material is improved, and the mechanical properties of the prepared ceramic substrate can be further improved. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the application.
[0029] In the following examples and comparative examples, the average particle size of magnesium oxide is 20 nm; the average particle size of calcium oxide is 40 nm; the average particle size of SiC powder is 30 μm; the length of zirconium oxide whisker is 30 μm, and the diameter is 3 μm; the type of polyethylene glycol is PEG-1000; and the type of polyvinyl butyral is TB-20.
[0030] Example 1 The preparation method of the modified SiC particles comprises the following steps: A1, dispersing 1 g of SiC powder in 300 mL of ethanol, ultrasonicating for 30 min, adding 26 wt% of ammonia water to adjust the pH to 7.5, dropping 3 mL of tetraethyl orthosilicate at a speed of 0.15 mL / min, stirring at 40℃ for 4.5 h, centrifuging, alcohol washing, and drying to obtain SiO2-coated SiC particles; A2, 1g SiO2-coated SiC particles were dispersed in 100mL water, 10mL acetic acid-sodium acetate buffer solution was added, then 100mL Al(NO3)3 solution with a concentration of 0.15mol / L was added dropwise at a speed of 3mL / min, ultrasonic, stirring, then 26wt% ammonia water was added to adjust the pH to 6.5, and it was kept at 70℃ for 40min, alcohol washing, drying to obtain modified SiC particles; A method for preparing a low warpage multilayer ceramic substrate, comprising the following steps: S1, 90 parts of alumina, 3 parts of cetyltrimethylammonium bromide, 4 parts of polyethylene glycol, 10 parts of polyvinyl butyral, 3 parts of magnesium oxide, 70 parts of ethanol, 6 parts of modified SiC particles were mixed, and then flow casting, drying to obtain a green ceramic sheet; S2, the green ceramic sheet was punched, filled, then surface printed, laminated 40 layers, pressed, up and down conductive, cut, sintered at 1600℃ for 4h, and cooled to obtain a low warpage multilayer ceramic substrate.
[0031] Example 2 A method for preparing modified SiC particles, comprising the following steps: A1, 1g SiC powder was dispersed in 300mL ethanol, ultrasonic for 30min, 26wt% ammonia water was added to adjust the pH to 9.5, and 5mL tetraethyl orthosilicate was added dropwise at a speed of 0.2mL / min, stirring at 50℃ for 4h, centrifugation, alcohol washing, drying to obtain SiO2-coated SiC particles; A2, 1g SiO2-coated SiC particles were dispersed in 100mL water, 10mL acetic acid-sodium acetate buffer solution was added, then 110mL Al(NO3)3 solution with a concentration of 0.15mol / L was added dropwise at a speed of 3.5mL / min, ultrasonic, stirring, then 26wt% ammonia water was added to adjust the pH to 7.5, and it was kept at 80℃ for 30min, alcohol washing, drying to obtain modified SiC particles; A method for preparing a low warpage multilayer ceramic substrate, comprising the following steps: S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 9 parts of modified SiC particles were mixed, and then flow casting, drying to obtain a green ceramic sheet; S2, the green ceramic sheet was punched, filled, then surface printed, laminated 40 layers, pressed, up and down conductive, cut, sintered at 1600℃ for 4h, and cooled to obtain a low warpage multilayer ceramic substrate.
[0032] Example 3 A method for preparing modified SiC particles, comprising the following steps: A1, 1 g SiC powder was dispersed in 300 mL ethanol, ultrasonic for 30 min, 26 wt% ammonia was added to adjust pH to 8.5, 4 mL tetraethyl orthosilicate was added dropwise at a speed of 0.18 mL / min, stirred at 40℃ for 4 h, centrifuged, alcohol washed, and dried to obtain SiO2-coated SiC particles; A2, 1 g SiO2-coated SiC particles were dispersed in 100 mL water, 10 mL acetic acid-sodium acetate buffer solution was added, 105 mL Al(NO3)3 solution with a concentration of 0.15 mol / L was added dropwise at a speed of 3.2 mL / min, ultrasonic, stirred, 26 wt% ammonia was added to adjust pH to 7, and incubated at 75℃ for 35 min, alcohol washed, and dried to obtain modified SiC particles; A method for preparing a low-warp multilayer ceramic substrate, comprising the following steps: S1, 100 parts of alumina, 3.5 parts of cetyltrimethylammonium bromide, 5 parts of glycerol, 11 parts of polyvinyl butyral, 3.5 parts of calcium oxide, 75 parts of isopropyl alcohol, and 7 parts of modified SiC particles were mixed, and then cast into a green ceramic sheet by tape casting and drying; S2, the green ceramic sheet was punched, filled, printed, laminated, and compressed to 40 layers, and then subjected to surface printing, lamination, and compression, upper and lower conduction, cutting, sintering at 1600℃ for 4 h, and cooling to obtain a low-warp multilayer ceramic substrate.
[0033] Example 4 The difference between this embodiment and Example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropyl alcohol, 4.5 parts of modified SiC particles, and 4.5 parts of zirconia whiskers were mixed, and then cast into a green ceramic sheet by tape casting and drying.
[0034] Example 5 The difference between this embodiment and Example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropyl alcohol, 3 parts of modified SiC particles, and 6 parts of zirconia whiskers were mixed, and then cast into a green ceramic sheet by tape casting and drying.
[0035] Example 6 The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet.
[0036] Example 7 The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 2.5 parts of modified SiC particles, and 6.5 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet.
[0037] Example 8 The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 6 parts of modified SiC particles, and 3 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet.
[0038] Comparative Example 1 The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet. The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet.
[0039] Comparative Example 2 The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet. The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet. The difference between this example and example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, 3.6 parts of modified SiC particles, and 5.4 parts of zirconia whiskers are mixed, and then cast molding, drying to obtain green ceramic sheet.
[0040] Comparative Example 3 The difference between the present comparative example and Example 2 is only that the modified SiC particles are replaced by SiC powder in the preparation of the low warpage multilayer ceramic substrate.
[0041] Comparative Example 4 The difference between the present comparative example and Example 2 is only that in step S1, 110 parts of alumina, 4 parts of cetyltrimethylammonium bromide, 3 parts of polyethylene glycol, 3 parts of glycerol, 12 parts of polyvinyl butyral, 2 parts of magnesium oxide, 2 parts of calcium oxide, 40 parts of ethanol, 40 parts of isopropanol, and 9 parts of zirconia whiskers are mixed by weight, and then cast, dried to obtain a green ceramic sheet.
[0042] Experimental Example 1 The low warpage multilayer ceramic substrates prepared in Examples 1-8 and Comparative Examples 1-4 were respectively tested for mechanical properties: Fracture toughness: the test method was three-point bending according to the test method specified in GB / T 23806-2009 “Fine Ceramics Fracture Toughness Test Method Single Edge Pre-cracked Beam (SEPB) Method”; Bending strength: the test method was three-point bending according to the test method specified in GB / T 6569-2006 “Fine Ceramics Bending Strength Test Method”; The results are shown in Table 1 below.
[0043] Table 1 Mechanical property test results
[0044] By comparing the data of Example 2 with Comparative Examples 1-3, the fracture toughness and bending strength of the multilayer ceramic substrate prepared by using silicon dioxide and alumina to modify SiC particles in Example 2 are significantly increased compared with Comparative Examples 1-3, which indicates that the use of silicon dioxide and alumina to modify SiC particles can significantly improve the mechanical properties of the prepared multilayer ceramic substrate.
[0045] By comparing the data of Example 2, Example 4~8, Comparative Example 4, it can be found that the fracture toughness and the bending strength of the multilayer ceramic substrate prepared by using the modified SiC particles and the zirconia whiskers in combination are significantly increased compared with Example 2 and Comparative Example 4, which indicates that the mechanical properties of the prepared multilayer ceramic substrate can be improved by using the modified SiC particles and the zirconia whiskers in combination; and by comparing the data of Example 4~8, it can be found that the fracture toughness and the bending strength of the multilayer ceramic substrate prepared by adjusting the mass ratio of the modified SiC particles and the zirconia whiskers are further increased compared with Example 7~8, which indicates that the mechanical properties of the prepared multilayer ceramic substrate can be further improved by adjusting the mass ratio of the modified SiC particles and the zirconia whiskers, and when the mass ratio of the modified SiC particles and the zirconia whiskers is 1:1~2, the mechanical properties of the prepared multilayer ceramic substrate can be further improved.
[0046] Experimental Example 2 The low warpage multilayer ceramic substrates prepared in Example 1~3 were respectively tested for warpage, and the results are shown in Table 2: Warpage: the warpage was tested by using a plug gauge measurement method; the testing method includes the following steps: using a plug gauge to start from one corner of the substrate, inserting the plug gauge, measuring the height of the corner, and then sequentially measuring the heights of the other corners of the substrate, and recording the height values of each corner.
[0047] Warpage: the ceramic substrate was freely placed on a plane, the height differences of the four corners and the center were measured, and the warpage was calculated according to the following formula:
[0048] In the above formula, δmax is the maximum height difference, δmin is the minimum height difference, and L is the diagonal length of the ceramic substrate.
[0049] Table 2: Test results of warpage
[0050] It can be found from the data in Table 2 that the warpage of the ceramic substrate prepared by the present application is ≤0.13%, which indicates that the ceramic substrate prepared by the present application has a low warpage.
[0051] The above only describes the preferred embodiments of the present application and is not intended to limit the present application, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A low-warpage multilayer ceramic substrate, characterized in that, The raw materials include the following parts by weight: 90-110 parts alumina, 3-4 parts dispersant, 4-6 parts plasticizer, 10-12 parts binder, 3-4 parts sintering aid, 70-80 parts solvent, and 6-9 parts functional additives; The functional additives include modified SiC particles; The modified SiC particles are obtained by sequentially coating SiC particles with SiO2 and Al2O3.
2. The low-warpage multilayer ceramic substrate according to claim 1, characterized in that, The method for preparing the modified SiC particles includes the following steps: A1. Disperse SiC powder in ethanol, add ammonia to adjust the pH to 7.5~9.5, add tetraethyl orthosilicate dropwise, stir, centrifuge, wash with alcohol, and dry to obtain SiO2-coated SiC particles. A2. The SiO2-coated SiC particles are dispersed in water, a buffer solution is added, Al(NO3)3 solution is added dropwise, the mixture is sonicated, stirred, and then ammonia is added to adjust the pH to 6.5-7.
5. The mixture is kept warm, washed with alcohol, and dried to obtain modified SiC particles.
3. The low-warpage multilayer ceramic substrate according to claim 2, characterized in that, In step A1, the stirring temperature is 40~50℃ and the stirring time is 4~4.5h; In step A2, the heat preservation temperature is 70~80℃ and the time is 30~40min.
4. The low-warpage multilayer ceramic substrate according to claim 2, characterized in that, The mass-to-volume ratio of SiC powder to tetraethyl orthosilicate is 1g:3~5mL; The concentration of the Al(NO3)3 solution is 0.1~0.2 mol / L; The mass-to-volume ratio of the SiC particles coated with SiO2 to the Al(NO3)3 solution is 1g:100~110mL.
5. The low-warpage multilayer ceramic substrate according to claim 2, characterized in that, In step A1, the dropping rate of the tetraethyl orthosilicate is 0.15~0.2 mL / min; In step A2, the Al(NO3)3 solution is added at a rate of 3~3.5 mL / min.
6. The low-warpage multilayer ceramic substrate according to claim 1, characterized in that, The functional additives also include zirconium oxide whiskers; The mass ratio of the modified SiC particles to zirconia whiskers is 1:1~2.
7. The low-warpage multilayer ceramic substrate according to claim 1, characterized in that, The sintering aid includes one or both of magnesium oxide and calcium oxide; The solvent includes one or both of ethanol and isopropanol.
8. The low-warpage multilayer ceramic substrate according to claim 1, characterized in that, The dispersant comprises hexadecyltrimethylammonium bromide; The plasticizer includes one or both of polyethylene glycol and glycerin.
9. The low-warpage multilayer ceramic substrate according to claim 1, characterized in that, The adhesive includes polyvinyl butyral.
10. A method for preparing a low-warpage multilayer ceramic substrate, used to prepare the low-warpage multilayer ceramic substrate according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. After mixing the raw materials, cast them into a mold, and then dry them to obtain raw ceramic tiles; S2. The raw ceramic sheet is punched and filled, and then subjected to surface printing, lamination, top and bottom connection, cutting, sintering and cooling to obtain a low warpage multilayer ceramic substrate.
Citation Information
Patent Citations
Nanometer composite powder of silicon carbide / aluminum oxide-calcium oxide core-shell structure and preparation method
CN101337819A
Composite abrasive grain in grain / alumina core-shell structure and preparation method and application of composite abrasive grain
CN102719220A
Sic@SiO<2> core-shell-structured nanofiller / epoxy resin-based composite material and preparation method thereof
CN110938288A
Preparation method of alumina ceramic material and alumina ceramic substrate
CN113185268A
Preparation method of SiC ceramic powder
CN113788683A